Effect of SGLT-1/2 inhibition on mitochondrial dysfunction in left atrial remodeling during HFpEF. (25th November 2020) - Bode, D; Semmler, L; Hegemann, N; Primessnig, U; Wakula, P; Pieske, B.M; Messroghli, D; Heinzel, F.R; Hohendanner, F
Abstract: Background: In the DAPA-HF trial, SGLT inhibition reduces cardiovascular mortality in heart failure. However, the mechanism and a potential positive effect in HfpEF remain elusive. Introduction: LA remodeling is a hallmark feature of HFpEF and commonly associated with LA enlargement and dysfunction. Previous studies of SGLT-2 inhibitor Empagliflozin suggest a utilization of alternative metabolites for energy consumption (i.e. ketone bodies). Additionally, alterations of sodium and calcium ion hemostasis have been reported. We investigated the effect of SGLT inhibition on mitochondrial (dys)function during atrial remodeling in HFpEF. Methods: Rats (WT: Wistar Kyoto, HFpEF: ZFS-1 Obese (metabolic syndrome)) were obtained at ∼10w and fed Purina 5008 diet. At 17w, animals were randomized to treatment with either vehicle or Sota (30mg/kg/d) for 5w until primary adult cardiomyocytes were isolated for final experiments. Structural information of mitochondria was obtained with Mitotracker Red in either a glucose starved (1h incubation with mannitol) or saturated state. ROS production was assessed with H2-DCF in a starved and saturated condition. Mitochondrial calcium buffer capacity was imaged with Rhod-2 following perforation of the cellular membrane with saponin. Glycolytic dependency of calcium cycling was assessed upon glycolytic inhibition with 2-deoxyglucose during imaging of cytosolic calcium transients with Fura-2. Results: In a glucose saturated state, LA cardiomyocytes in HFpEF showed increased mitochondrial density, which was ameliorated with Sota. Sota increased mitochondrial calcium buffer capacity in HFpEF, indicating a decrease in mitochondrial resting calcium. Differences in mitochondrial fission could not be detected. However, during glucose starvation cardiomyocytes showed a decrease in mitochondrial fission and ROS production with Sota. A difference in ROS production was not visible when cells were abruptly challenged with high glucose concentrations, but Sota decreased mitochondrial fission, indicating long term protective properties towards ROS. Glycolytic inhibition led to an increase of cytosolic diastolic calcium and calcium transient peak height in HFpEF vs. WT, indicating an increased glucose dependency of cytosolic calcium cycling, which was mitigated with Sota. Additionally, Sota negated an increase in diastolic calcium, when cardiomyocytes where challenged with high concentrations of glucose after starvation. Conclusion: SGLT1/2 inhibition alters mitochondrial calcium uptake in HFpEF and positively affects mitochondrial structure with subsequent decreases of ROS production and enhanced calcium homeostasis. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Else-Kröner-Fresenius-Stiftung, Deutsches Zentrum für Herz-Kreislaufforschung